KOMIK IKLAN KOMIK - Wibowo Tamsir (DeKaVe, 2019)
Comics are a form of visual art that uses still images and is arranged in such a way in several panels that make up the fabric of the story. While Cergam is a picture that has served as an illustration in a series of stories. The types of comics that are rarely included in large groups of comics, namely Advertising Comics. Like Indie Comics, it's quite surprising why comic designers don't think about it. For certain types of products that are not too serious in advertising information, comics turn out to be a potential medium. Especially for the target audience of young people who prefer visual and entertaining images such as comics. Maybe because it is considered advertising was born from business needs. Not a pure work of art. Therefore "comic advertisements" are included in the category of public service media. Some famous comic artists are often "used" by producers to draw advertisements. The audience immediately recognized the painter by the way he told stories, the character's figures and the style of his strokes.